Occupational acne: a case series - Kumar, Ravi; Smita, Kumari; Singh, Rohit Kumar; Prasad, Jawahar; Shankar, Vikas; Sinha, Rani Indira (International Journal of Basic & Clinical Pharmacology, 2024)
Occupational acne a type of acne venenata, is caused by both the action of physical environmental factors and professional contact with chemicals. It can affect both those who have pre-existing seborrhea and acne that gets worse after chemotherapy and those who do not have a positive history of these conditions. Previously, occupational acne was believed to be one of the most common environmental skin conditions, second only to contact dermatitis. Although specific risk factors are not required, oil acne and cystic acne may be influenced by a predisposition to seborrhea and a history of hepatic alteration. From an etiological perspective, there are two types of occupational acne: petroleum-derived acne and acne resulting from coal tar products. In Skin and VD department OPD, Patna Medical College and Hospital we got three cases of occupational acne in February 2024. We came to the conclusion that these were occupational acne on the basis of detailed enquiry about previous chemical exposure and histopathological examinations. These patients were advised to immediate cessation of chemical exposure and managed by appropriate antibiotics, isotretinoin and face hygiene. All patients recovered satisfactory without any complications in 10-12 weeks.